(a+2)=(3a+9)

Simple and best practice solution for (a+2)=(3a+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+2)=(3a+9) equation:


Simplifying
(a + 2) = (3a + 9)

Reorder the terms:
(2 + a) = (3a + 9)

Remove parenthesis around (2 + a)
2 + a = (3a + 9)

Reorder the terms:
2 + a = (9 + 3a)

Remove parenthesis around (9 + 3a)
2 + a = 9 + 3a

Solving
2 + a = 9 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
2 + a + -3a = 9 + 3a + -3a

Combine like terms: a + -3a = -2a
2 + -2a = 9 + 3a + -3a

Combine like terms: 3a + -3a = 0
2 + -2a = 9 + 0
2 + -2a = 9

Add '-2' to each side of the equation.
2 + -2 + -2a = 9 + -2

Combine like terms: 2 + -2 = 0
0 + -2a = 9 + -2
-2a = 9 + -2

Combine like terms: 9 + -2 = 7
-2a = 7

Divide each side by '-2'.
a = -3.5

Simplifying
a = -3.5

See similar equations:

| -25+2x=32-x | | .07x+84532=x | | -94+x=81-6x | | (3x-1)=(5x-2) | | 136=Y(X*4-7) | | 4y=4x+2 | | 3(5x-4)-(3x+2)=16 | | 9x=5x+56 | | 4(t-2)+6t=5(2t+2)-9 | | 2x^2+3=-6x | | 9x=5x+55 | | 15-a+5a=5 | | 3x-4x=8-3 | | -7(2x-4)+5x=5(x+6) | | (x+4)=(2x+5) | | c=10-2.5 | | (x+5)=(x-9) | | y=10-2.5 | | -6(-4u+4)-5u=3(u-4)-2 | | 15-(-47)= | | 6(x-1)=-3(2-x)+3 | | -16t^2+128t+16.25=0 | | -6(y+2)=3y-9+3(2y+5) | | -x^2+3x+8=0 | | 3+7+6=2x+5+5x | | (-b^3)(d^2)=0 | | -4(v+1)=-6v-22 | | SolveV=lwhforH | | 3u-9=17(u-3) | | (4+x)+2= | | 650=0.3536x+14.857 | | 8(v+2)=-8v+32 |

Equations solver categories